2004
DOI: 10.1159/000076015
|View full text |Cite
|
Sign up to set email alerts
|

Stratum Corneum Maturation

Abstract: The importance of the stratum corneum and its barrier function for infants, especially for newborns, is clinically evident. Research regarding the maturation of the stratum corneum in neonates, i.e. when full barrier function is obtained, has produced varying results. Based on transepidermal water loss and percutaneous absorption studies, term infants seem to possess stratum corneum with adult barrier properties. Additionally, postnatal life is thought to accelerate stratum corneum maturation, so that even pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(66 citation statements)
references
References 154 publications
0
63
1
2
Order By: Relevance
“…In preterm infants, TEWL is higher than in full-term neonates at birth and decreases at a slower rate [1,2,4,23,24]. During this study, TEWL remained stable at all investigational sites in group C, indicating a lack of barrier maturation [2].…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In preterm infants, TEWL is higher than in full-term neonates at birth and decreases at a slower rate [1,2,4,23,24]. During this study, TEWL remained stable at all investigational sites in group C, indicating a lack of barrier maturation [2].…”
Section: Discussionmentioning
confidence: 94%
“…One study in very preterm infants showed that topical ointment decreased TEWL, without documenting other skin functional parameters [14]. Yet, the neonatal skin barrier depends on a balance between functional parameters, such as TEWL, SCH, skin pH and sebum, and entails anatomical variability [1,16,17,18,21]. To our knowledge, this is the first prospective study objectively assessing postnatal skin barrier properties at different anatomical sites in otherwise healthy preterm infants under adequate neonatal therapy and monitored ambient conditions not only during, but also after the stop of SSO application.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In premature newborns of <32 weeks of gestational age, stratum corneum is very thin. Such immature stratum corneum does not suffi ciently prevent transepidermal water loss, absorption of external agents and invasion of microbes (1)(2)(3)(4)(5)(6)(7)(8)(9). Birth with exposure to external environment stimulates and accelerates maturation of epidermal barrier in prematures.…”
Section: Developmental and Functional Features Of Very Premature Skinmentioning
confidence: 99%